The Size of the Crypto Economy: Calculating Market Shares of Cryptoassets, Exchanges and Mining Pools. (25th June 2020) - Stylianou, Konstantinos; Carter, Nic
Abstract: Cryptoassets and related actors such as crypto exchanges and mining pools are now fully integrated into mainstream economic activity. A necessary corollary is that they have attracted heightened regulatory and investor scrutiny. Although some rules and obligations apply uniformly across all economic actors in a given sector, many others, such as antitrust laws and some financial regulations as well as investor decisions are informed by actors' relative economic size—meaning that those with larger market shares can become more attractive regulatory or investing targets. It is therefore a foundational issue to properly measure the economic footprint of economic actors in the crypto economy, for otherwise regulatory oversight and investor decisions risk being misled. This has proven a remarkably difficult exercise for multiple reasons including unfamiliarity with the underlying technology and role of involved actors, lack of understanding of the applicable metrics' economic significance, and the unreliability of self-reported statistics, partly enabled by lack of regulation. Acknowledging the centrality of cryptoasset size in a number of regulatory and policymaking areas and the fact that previous attempts have been incomplete, simplistic, or even plainly wrong, this paper presents the first systematic examination of the economic footprint of cryptoassets and their constituent actors—mining pools and crypto exchanges. We aim to achieve a number of objectives: to introduce, identify, and organize all relevant and meaningful metrics of crypto economic actors market share calculation; to develop associations between metrics, and to explain their meaning, application, and limitations so that it becomes obvious in which context metrics can be useful or not, and what the potential caveats are; and to present rich, curated, and vetted data to illustrate metrics and their use in measuring the shares of crypto economic actors in their respective markets. The result is a comprehensive guidance into the size of the crypto economy.